The Psychology of Deception: Why We Believe Deepfakes - Plohl, Nejc; Smrke, Urška; Aquilino, Letizia; Mlakar, Izidor (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
Advances in artificial intelligence have enabled the creation of highly realistic deepfakes, yet their impact ultimately depends on how humans perceive and interpret them. This chapter examines the psychological processes underlying belief in deepfakes, focusing on perceptual mechanisms, individual differences, and downstream consequences. Despite widespread confidence in detection abilities, people generally struggle to distinguish authentic from manipulated videos, often performing at or near chance. To move beyond binary detection measures, we introduce the construct of perceived trustworthiness, defined as the extent to which a video is experienced as authentic. We describe the development and validation of the Perceived Deepfake Trustworthiness Questionnaire (PDTQ), which captures two dimensions: trustworthiness of content (plausibility and source credibility) and trustworthiness of presentation (perceived realism of delivery, including technical quality, voice, and behaviour). This tool enables systematic examination of perceptual features that make deepfakes believable across contexts. We further show how sociodemographic, motivational, and cognitive factors shape susceptibility, and demonstrate that perceived trustworthiness predicts attitudes toward climate change and immigration as well as intentions to share content. Overall, the chapter highlights the need for psychological, not only technological, interventions.